Intelligence and abilities - Cooper, Colin, 1954- (Psychology focus., 2008)
Research into abilities is one of the great success stories of psychology. Ability tests are widely used and there is continued interest in the origins of abilites (enes or environment?) and their links to social phenomena such as crime and welfare dependecy. Intelligence and Abilities explains what is known about the processes associated with mental abilities and the relationship of abilities to behaviour. It also provides a clear and up-to-date guide to the main areas of research.